Effectiveness of Giving Aloe Vera Juice on Changes in Blood Pressure in Family Members With Hypertension Quasi Experimental Family Nursing - Nurni Nurmaliyati; Opiyani Sukmawati (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Hypertension is a global health problem that increases in older adults and serves as a risk factor for cardiovascular diseases. In DKI Jakarta, the highest prevalence of hypertension occurs in the 50–70-year age group, particularly among women. Management can be carried out through pharmacological and non-pharmacological therapies, including Aloe vera juice, which contains bioactive compounds with vasodilatory and antioxidant properties.Objective: This study aimed to determine the effectiveness of Aloe vera juice in altering blood pressure among family members with hypertension. Methods: This research employed a quasi-experimental one-group pre-test and post-test design to evaluate the effect of Aloe vera juice on blood pressure in 25 family members with hypertension at Puskesmas Jatinegara, East Jakarta. Data were collected by measuring blood pressure before and after a 7-day intervention and from patient medical records. Data analysis was conducted using univariate and bivariate methods, applying the Wilcoxon Signed Rank Test with a significance level of p ≤ 0.05 to determine the effectiveness of the intervention. Results: The study found that Aloe vera juice reduced systolic blood pressure in family members with hypertension, from a median of 157 mmHg to 136 mmHg (Δ 21 mmHg). It also lowered diastolic blood pressure, from a median of 93 mmHg to 83 mmHg (Δ 10 mmHg). The Wilcoxon test showed that Aloe vera juice significantly reduced blood pressure in family members with hypertension (Z = -3.962; p = 0.000). Conclusion and Recommendations: Aloe vera juice was proven to significantly reduce both systolic and diastolic blood pressure in family members with hypertension, indicating a significant difference between pre- and post-intervention blood pressure. Aloe vera juice can be used as a non-pharmacological intervention to lower blood pressure. Future studies are recommended with larger sample sizes and a randomized controlled trial (RCT) design, and family education programs can be implemented to support hypertension management at home.